Numerical Study on the Tortuosity of Porous Media via Lattice Boltzmann Method (Communications in Computational Physics, 2018)
In this paper, we simulate the pressure driven fluid flow at the pore scalelevel through 2-D porous media, which is composed of different curved channels viathe lattice Boltzmann method. With this direct simulation, the relation between the tortuosityand the permeability is examined. The numerical results are in good agreementwith the existing theory.